HERITAGE POLICIES AND DISPOSSESSION PROCESSES AND VIOLENCE IN LATIN AMERICA - Saldi, Leticia (Instituto Regional de Planeamiento y Hábitat (RPHA), Unidad Doble dependencia CONICET y UNSJ, 2023)
In recent years, heritage processes have gone through a critical turn that demonstrates the difficulties in carrying out democratic, consensual and egalitarian ways of deciding what and how to care for or preserve. Accounting for the racist, elitist and patriarchal ways with which even national states conceive their identity and internal diversity also implies reflecting on the exercise of disciplines, such as archeology and anthropology, and their scientific methods and theories. This looking inward requires rethinking the relationship between professionals with the spheres of the state, with mainly indigenous social organizations and with the territories as a whole. The book Patrimonial Policies and Processes of Dispossession and Violence in Latin America is part of this critical review of patrimonialization and disciplinary fields.